From Constraint to Agency: The Phenomenology of EFL Writing Development in Process-Oriented Pedagogy - Putri, Hikmah Zalifah; Herizal, Herizal; Marzulina, Lenny; Erlina, Dian; Holandyah, Muhammad; Dwiana, Nadya Rezkhita (Edukasi, 2025)
Writing remains one of the most demanding skills for EFL learners, who often face difficulties in generating ideas, organizing content, and producing coherent and accurate texts. This study aimed to explore EFL students’ writing practices through a qualitative thematic analysis of their engagement in the writing process identify recurring patterns in students’ writing behaviors and perceptions.The participants were third-semester university students enrolled in an Intermediate Writing course. Data were collected through classroom observations, student reflections, questionnaires, and teacher journals, and analyzed thematically. Findings revealed three major themes: (1) the evolving awareness of writing as a recursive process, (2) the development of self-regulated strategies during revising and editing, and (3) the emergence of more positive attitudes toward writing. The thematic analysis suggests that implementing the writing process supports learners’ writing development not only in terms of textual quality but also in their metacognitive engagement and confidence as writers. The study highlights the pedagogical value of process-oriented instruction in fostering meaningful writing practices in EFL classrooms.